2012
DOI: 10.1186/1476-5926-11-4
|View full text |Cite
|
Sign up to set email alerts
|

N-acetylcysteine improves antitumoural response of Interferon alpha by NF-kB downregulation in liver cancer cells

Abstract: BackgroundLiver cancer is one of the most common malignancies in the world and at the moment, there is no drug intervention effective for the treatment of liver tumours. Investigate the effect of N-acetylcysteine (NAC), which has been studied for its antitumoural properties, on the toxicity of hepatocarcinoma (HCC) cells in vitro when used with the drug interferon alpha-2A (IFN), which is used clinically to treat HCC.ResultsNAC, IFN and NAC plus IFN reduced cell viability, as determined by MTT assay. More impo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 51 publications
1
22
0
Order By: Relevance
“…Since NF‐κB p50 is produced as a proteolytic product of the pre‐form NF‐κB1 (p105), for qualitative purpose, the inhibitory effect of β‐eudesomol on NF‐κB (p50) expression was considered as the representative measure of NF‐κB1/p50 downregulation. Similar studies involving chemostress‐induced downregulation of NF‐κB (p65) protein have previously been employed to access the inhibitory effects of various compounds on NF‐κB expression in leukemic T and hepatic cancer cells . Taken together, the inhibitory effect of β‐eudesmol on the production of cytoprotective enzymes and stimulatory effect on the expression of key transcriptional factor proteins may be linked to the observed cytotoxicity of the compound on CL‐6 cells.…”
Section: Discussionmentioning
confidence: 85%
“…Since NF‐κB p50 is produced as a proteolytic product of the pre‐form NF‐κB1 (p105), for qualitative purpose, the inhibitory effect of β‐eudesomol on NF‐κB (p50) expression was considered as the representative measure of NF‐κB1/p50 downregulation. Similar studies involving chemostress‐induced downregulation of NF‐κB (p65) protein have previously been employed to access the inhibitory effects of various compounds on NF‐κB expression in leukemic T and hepatic cancer cells . Taken together, the inhibitory effect of β‐eudesmol on the production of cytoprotective enzymes and stimulatory effect on the expression of key transcriptional factor proteins may be linked to the observed cytotoxicity of the compound on CL‐6 cells.…”
Section: Discussionmentioning
confidence: 85%
“…Interestingly, the cytokines stimulation did not significantly affect total NF‐κB expression in CL‐6 cells, but atractylodin treatment moderately downregulated the key NF‐κB proteins in a dose‐dependent manner. Chemical‐induced down‐regulation of the p65 NF‐κB protein has previously been used to investigate the collective inhibitory effect of various chemicals on NF‐κB expression in hepatic cancer cells . The baseline level of the p100 NF‐κB protein was undetectable (data not shown), which may be due to the altered or abnormally high levels of phosphorylation‐dependent ubiquitination and processing of p100 protein in CL‐6 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Activation of NF-κB in response to various signals, including IL-1, TNF and H2O2 can be inhibited by NAC treatment, suggesting that ROS are common signaling modulators [258] . Moreover, NAC was found to enhance the effect of IFN-α on liver tumor cells through inhibition of NF-κB [259] . On the other hand, some studies suggested that NAC inhibits the upstream IKK activation induced by TNF-α [260] .…”
Section: Of Viral Infectionsmentioning
confidence: 99%